The examination of Giresun city parks in terms of landscape design criteria - Ayhan, Afşin; Atabeyoğlu, Ömer (Ege Üniversitesi, 2021)
Objective: The main objective of this study was to evaluate Giresun city parks from various aspect such as environmental relations, transportation possibilities, utilization of functional area, equipments, planting, utilization of functional plants and utilization of the park, determine the qualitative and quantitative characteristics thereof and demonstrate their competence in requirements of the people.Material and Methods: The parks were ranked out of 540 points that could be given to the design criteria and compared with each other so that many parks could be evaluated objectively. Furthermore, the parks were classified in the light of literature information (24 playgrounds, 14 neighborhood parks, 4 city parks and 1 sports field), and their competence were provided in terms of recommended standard values in tabular data.Results: It was determined that in 33 of the parks, there was no variety in terms of age groups in children's playground equipment while there were no units such as indoor seating, lighting elements and ramps at the entrance points in 22, 13 and 9 of the city's parks, respectively. Furthermore, it was detected that the number of parking space requirement was not enough to meet the requirements and squalidity as well as the lack of shade in some parks lead to discomfort, and the total score average for all parks was calculated to be 191.1 (35.3%).Conclusion: Consequently, the requirement for a new city-specific design guide was revealed by virtue of the deficiencies found in the current situation and recommendations that can help local governments or designers for the future were developed.

Amaç: Giresun kenti parklarını çevresel ilişkiler, ulaşım olanakları, fonksiyonel alan kullanımı, donatılar, bitkilendirme, fonksiyonel bitki kullanımı ve park kullanımı ile çok yönlü olarak değerlendirmek, nitel ve nicel özelliklerin tespiti ile halkın ihtiyaçları bakımından yeterliliklerinin ortaya konulabilmesi çalışmanın ana ilgi odağıdır.Materyal ve Yöntem: Arazi gözlem ve değerlendirme formu yardımıyla Giresun’da yer alan 43 adet park yerinde incelenerek puanlanmıştır. Parklar tasarım kriterlerine verilebilecek toplamda 540 puan üzerinden sıralamaya tabi tutulmuş, birbirleri ile kıyaslanmış ve parklar nesnel bir şekilde yorumlanabilmiştir. Ayrıca literatür bilgileri ışığında parklar sınıflandırılmış olup (24 çocuk bahçesi, 14 mahalle parkı, 4 kent parkı ve 1 spor alanı), önerilen standart değerler açısından yeterlilikleri de tablosal veri halinde sunulmuştur.Araştırma Bulguları: Parklarının 33’ünde çocuk oyun ekipmanlarında yaş grupları açısından çeşitliliğin, 22’sinde kapalı oturma birimlerinin, 13’ünde aydınlatma elemanın, 9’unun giriş noktalarında rampa vb. sağlanmadığı tespit edilmiştir. Ayrıca sayısal olarak park alanı gereksiniminin karşılanmadığı, bazı parklarda bakımsızlık ile gölge ihtiyacının karşılanamamasının rahatsızlık yarattığı, tüm parklar içinse toplam puan ortalamasının 191.1 (%35.3) olduğu tespit edilmiştir.Sonuç: Sonuç olarak; mevcut durumda gözlenen eksiklikler ile kente özgü yeni bir tasarım rehberinin gerekliliği ortaya konulmuş, geleceğe yönelik yerel yönetimler veya tasarımcılara yardımcı olabilecek öneriler geliştirilmiştir.
Keywords: Engineering; Açık ve yeşil alanlar; Giresun; Parklar; Kentsel tasarım; Mühendislik; Open-green spaces; Giresun; Parks; Urban design